Possibility of using immersion cooling technology with virgin coconut oil for split-type AC - Achmad Wibolo; I Wayan Temaja; Ida Bagus Gde Widiantara; Made Ery Arsana; M. Yusuf (Universitas Mercu Buana, 2026)
Conventional split-type air conditioners are limited by high electrical consumption, noise from cooling fans, and bulky condenser coils that restrict installation flexibility. However, the application of immersion cooling in household AC systems remains largely unexplored. This study investigates the feasibility of using Virgin Coconut Oil (VCO) as a dielectric fluid for immersion cooling to improve energy efficiency and thermal performance. An experimental setup was developed using 20 L of SNI-compliant VCO, with the outdoor unit modified for immersion operation. Key performance parameters, including condenser coil and evaporator coil temperatures and the Coefficient of Performance (COP), were measured. Results showed condenser coil temperatures ranging from 40 °C to 58 °C and evaporator coil temperatures between 6 °C and 11 °C. The system achieved an average COP of 4.65 and reduced electrical consumption by approximately 20 %, indicating significant energy savings without compromising cooling efficiency. VCO also demonstrated suitable dielectric properties, with a breakdown voltage of 29.17 kV, near the IEC 156 threshold. These findings highlight immersion cooling with VCO as a promising, quiet, and energy-efficient alternative for household air conditioners. Further work is recommended to assess long-term reliability under varying operational conditions.